PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN CV. MAJU JAYADI TRANSPORT KECAMATAN SANDUBAYA, KOTA MATARAM - Mochamad Ronald Galih R; Thatok Asmony; Mukmin Suryatni (Master of Management, Mataram University, 2023)
The study aims to analyze the effects of compensation and work environment on the job satisfaction of CV Maju Jayadi Transport's employee. The respondents in this study are 60 people. The type of research used is associative research. The method of collecting data used was the census method. The data analysis technique used is linear regression analysis used used SPSS version 16.0. Research shows that: (1) compensation has a positive and significant impact on the job satisfaction of the employee of the CV Maju Jayadi Transport's employee, (2) the work environment has a positive and significant impact on the employment satisfaction CV Maju Jayadi Transport's employee. Based on the results of this research, there can be a link between compensation and the working environment toward the working title of CV Maju Jayadi Transport employee.